Semantic field analysis and the structure of culture: a comparative study of Sotho and Xhosa - Thipa, Henry Mothebesoane (Rhodes University, Faculty of Humanities, School of Languages, 1980)
Analyses of Sotho and Xhosa seem to concentrate predominantly on morphological, tonological and phonological studies. Semantics seems to be a relatively neglected area in African Languages. It is the view of the writer that attention should now be turned increasingly to semantics. In fact, except perhaps for van Rooy's Venda work semantic field analysis does not seem to have been undertaken in African Languages. This thesis is an attempt to contribute in this particular area of linguistic analysis. In addition to that, the present study is an attempt to explore new dimensions in African language study, namely the application of componential analysis to two African languages, Sesotho and Xhosa. In general terns, the aim of the present study is to explore the relationship between language and culture. Very little seems to have been done in this particular area in African languages. In this connection the only work that comes to mind is van Rooy' s Venda work which has already been referred to above. In that work, van Rooy tries to show the integration of language and culture in the communication of the Christian message as illustrated by the Venda Bible. Perhaps with the notable exception of Siertsema there seems to be some scholarly concensus about the relationship between language and culture as the following brief survey will show. Boas, the American anthropologist, for example has investigated the interplay of the environment, cultural life and linguistic form. This be has done by comparing Kwakiutl, an American Indian language, with the Eskimo language. Lotz shows how the structure of one semantic field, or area of semantically related terms, namely numerals, can shape the goals a particular linguistic community strives for in a major cultural activity such as sports. Conklin shows how languages may differ not only in their segmentation of a semantic field e.g. colour, but also in the dimensions of semantic fields themselves. Siertsema, on the other hand, takes a different view from the above views. Only a brief summary of his views will be given here. A fuller exposition will be made in the next chapter when some theoretical issues are considered. He disputes the view that language and culture are related. It must be noted though that he does not speak specifically of culture but of a world view. He examines four "properties" of language and on their basis disputes the language - world view relationship which he eventually dismisses as showing circular reasoning. Perhaps another scholar that needs to be mentioned is Whorf who admittedly is not writing about semantic fields. His relevance to the present discussion lies in the fact that he also considers the relationship between language and other phenomena, namely thought. He writes, "We dissect nature along lines laid down by our native languages. The categories and types that we isolate from the world of phenomena we do not find there because they stare every observer in the face; on the contrary, the world is presented in a kaleidoscopic flux of impressions 'Which has to be organized by our minds - and this means largely by the linguistic systems in our minds. We cut nature up, organize it into concepts, and ascribe signfiicances as we do, largely because we are parties to an agreement to organize it in this way - an agreement that ... is codified in the patterns of our language". Whorf 's theory has been called the Dissection Theory from the opening line of the quotation that has just been referred to. Put in a nutshell, what Whorf is saying is that language has a constraining influence on thought or cognition. Or, perhaps put in another way, it is through language that reality is NECESSARILY apprehended. Thought and cognition have to be seen as necessarily dependent on language, at least in certain respects. Whorf discusses a linguistic - philosophic problem which is not really relevant to a study that addresses itself to semantic fields. In exploring the relationship between language and culture some semantic fields will be analyzed. A lexical analysis of each semantic field will then be done applying some of the insights and techniques of componential analysis. What this means, is that we shall start with vocabulary, analyze it and see through its structure the structured world of culture. The question may well be asked, why Sotho and Xhosa? Firstly, the reason for choosing these two languages is for comparison and contrast. Sotho and Xhosa belong to the same language area, traditionally known as the south-eastern zone. As a result, these two languages share certain morphological, syntactic and phonological phenomena. Because the present study is basically semantic one can also add that the choice of the two languages is meant to reveal the extent of semantic similarities and differences between them. Secondly, the writer is, so to speak, bi-cultural. He is very well acquainted with both Basotho and amaXhosa cultures firstly, because of the circumstances of his birth and secondly, because of his education. The writer is actually Sotho speaking with a Xhosa speaking mother. He also has university training in both Sotho and Xhosa, languages he can speak fluently. All these factors are mentioned here in order to lay some claim to competence in both Sotho and Xhosa. Basotho and amaxhosa live in slightly distinct worlds despite all linguistic affinities between their languages. They have slightly different perceptions of the same reality. This accounts for the difference in the organization of any selected field, however slight in some cases. This factor seems to be an indication of the fact that the conceptualization of the universe differs from language to language. This is the point that is also made by Hoijer and Lyons. Hoijer argues that the "real world" to a large extent depends, perhaps unconsciously , on the language habits of the speakers. He goes on to say that no two languages are so similar as to be considered to represent the same social reality. This naturally goes for Sotho and Xhosa as well. The world in which different peoples live are different and cannot merely be characterized as the same world with only different labels. Lyons is even more pertinent to the present study, ''Every language is integrated with the culture in which it operates; and its lexical structure reflects those distinctions which are (or have been) important in the cultures. This statement cannot be overemphasized. While the assumption will be held that language reflects culture, one may hasten to add that not every word in a language does so. For example, there does not seem to be anything particularly cultural about interjectives or about ideophones. In other words, some lexical items are more significant than others in this respect. One should therefore rather speak of lexical items as being a mirror of culture in 'a selective kind of way. As Hymes puts it, "In a particular culture a language serves as a sort of "metalanguage", a cultural way of communicating about much, not all of the culture". (Emphasis added).
Keywords: Xhosa language -- Semantics; Sotho language -- Semantics; Xhosa language -- Social aspects; Sotho language -- Social aspects; Field theory (Linguistics); Componential analysis (Linguistics)